Phylogenetic Uniqueness of Honeybee Apis Cerana from the Korean Peninsula Inferred from The Mitochondrial, Nuclear, and Morphological Data - Ilyasov, Rustem A.; Park, Junhyung; Takahashi, Junichi; Kwon, Hyung Wook (Journal of Apicultural Science, 2018)
is an Eastern honeybee species distributed throughout Asia and closely related to the Western honeybee species distributed across all of Africa, Europe and Western Asia, and subdivided into thirty confirmed subspecies. Currently, is an endangered bee species in contrast to We sequenced and annotated the complete mitochondrial genome of from the Jeollanam-do province of South Korea and uploaded to the DDBJ/Genbank database(AP018431). MtDNA sequence is 15.925 bp long, has 84% AT-content and 16% GC-content and contains 22 tRNA genes, 13 protein-coding genes, two ribosomal RNA genes, one AT-rich region and four non-coding intergenic regions ( ). All protein-coding genes are started by ATT and ATG codons, except the genes and , which started by ATC and ATA, respectively, and are stopped by the common codons TAA and TAG. A comparative analysis of the whole mtDNA sequences of from Korea and Taiwan, from China and from Japan showed that the genetic divergence of the Korean sample from subspecies (2.57%) and (2.58%) matched to the level of genetic divergence of mtDNA between animal subspecies (0.8-8%). Based on the comparative analysis of complete mtDNA (~16,000 bp), two nuclear gene and sequences (~8,000 bp) and morphological measurements (six parameters), we assumed that Korean , Chinese and Japanese are different subspecies at an early stage of sub-speciation and could be called further as subspecies of